Electrochemical biosensing based on noble metal nanoparticles - Wang, Jing (Mikrochimica acta (1966), 2012)
The interest in the fabrication of electrochemical biosensors with high sensitivity, selectivity and efficiency is rapidly growing. In recent years, noble metal nanoparticles (NMNPs), with extraordinary conductivity, large surface-to-volume ratio and biocompatibility, have been extensively employed for developing novel electrochemical sensing platforms and improving their performances. Through distinct surface modification strategies (e.g. self-assembly, layer-by-layer, hybridization and sol-gel technology), NMNPs provide well control over the microenvironment of biological molecules retaining their activity, and facilitate the electron transfer between the redox center of biomolecules and electrode surface. Moreover, NMNPs have been involved into biorecognition events (e.g. immunoreactions, DNA hybridization and ligand-receptor interactions) by conjugating with various biomolecules, chemical labels and other nanomaterials, achieving the signal transduction and amplification. The aim of this review is to summarize different strategies for NMNP-based signal amplification, as well as to provide a snapshot of recent advances in the design of electrochemical biosensing platforms, including enzyme/protein sensors focused on their direct electrochemistry on NMNP-modified electrode surface; immunosensors and gene sensors in which NMNPs not only participate into biorecognition, but also act as electroactive tags to enhance the signal output. In addition, NMNP alloy-based multifunctional electrochemical biosensors are briefly introduced in terms of their unique heterostructures and properties. Figure With the co-modification of hemoglobin and multi-layers of gold nanoparticles onto the gold electrode surface, gold nanoparticles facilitate the electron transfer between hemoglobin and electrode. As a result, the direct electrochemistry of hemoglobin could be obtained.